Health promotion and aging : practical applications for health professionals - Haber, David, 1944- (New York : Springer Publishing Company, 2020)
I was trained at the University of Southern California as a sociologist looking at the big picture and specializing in gerontology, but I spent my career implementing and evaluating small health promotion projects in the community. This divergence between training and practice has informed me on why promoting health is possible, but difficult. From a sociological perspective, it is clear to me that American society is not particularly health promoting. For example, computers are increasingly promoting sedentary behavior, both at work and at play. A fast-paced society encourages us to seek convenient food and drink choices, and ubiquitous advertising-to the tune of tens of billions of dollars per year-promotes questionable foods and drinks over good nutrition. And the considerable stress engendered by a dynamic society can lead to smoking, excessive alcohol consumption, or engaging in other risky behaviors.
Introduction to health promotion and aging -- Clinical preventive services and aging -- Empowering older adults -- Exercise and aging -- Nutrition, weight management, and aging -- Complementary and alternative medicine, and aging -- Selected health education and aging topics -- Mental health and aging -- Community health and aging -- Long-term care and end-of-life care -- Public health policy and aging -- Diversity and aging.
Includes bibliographical references and index.
Keywords: Health promotion; Aged; Aging; Preventive health services; Health services for the aged; Chronic disease -- Prevention & control